2015
DOI: 10.7314/apjcp.2015.16.8.3229
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Features of Triple-Negative Breast Cancer: a Comparison with Other Breast Cancer Subtypes

Abstract: Background: Triple-negative breast cancer (TNBC) is known to be associated with aggressive biologic features and a poor clinical outcome. Therefore, early detection of TNBC without missed diagnosis is a requirement to improve prognosis. Preoperative ultrasound features of TNBC may potentially assist in early diagnosis as characteristics of disease. Purpose: To retrospectively evaluate the sonographic features of TNBC compared to ER (+) cancers which include HER(-) and HER2 (+), and HER2 (+) cancers which are E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 13 publications
12
52
0
Order By: Relevance
“…Tumors with a high histological grade and high Ki‐67 expression are expected to have a high mitotic rate and short doubling time . The tumors are prone to be homogeneous with intensive cellularity, leading to less US wave attenuation and enhanced through‐transmission, which result in posterior echo enhancement . Meanwhile, a higher proliferation rate suggests rapid tumor growth and a more active metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors with a high histological grade and high Ki‐67 expression are expected to have a high mitotic rate and short doubling time . The tumors are prone to be homogeneous with intensive cellularity, leading to less US wave attenuation and enhanced through‐transmission, which result in posterior echo enhancement . Meanwhile, a higher proliferation rate suggests rapid tumor growth and a more active metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The US appearance depends on prognostic factors such as proliferation rate and hormone receptor status (55). Early-stage, fastgrowing, and more aggressive subtypes of IDC, such as triple-negative IDC and other high-grade IDCs, tend to be more round, have circumscribed or microlobulated margins, and show posterior acoustic enhancement (56)(57)(58)(59)(60) (Fig 15). Some of the more aggressive subtypes of IDC may therefore mimic benign lesions (55,56,58).…”
Section: Invasive Ductal Carcinomamentioning
confidence: 99%
“…lated margins, and show posterior acoustic shadowing (56,57,(59)(60)(61) (Fig 16). IDCs are therefore a heterogeneous group with a variety of US appearances.…”
Section: Invasive Ductal Carcinomamentioning
confidence: 99%
“…Triple negative breast cancer (TNBC) is a subtype of breast cancer where the cancer cells lack the estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2 (HER2) 34 . Out of total breast cancer cases 10 – 20% are TNBC cases and various studies showed the expression of specific miR pattern in these cases which can act as biomarker for cancer diagnosis 30 , 35 , 36 .…”
Section: Mirs Controlling Involution and Breast Cancermentioning
confidence: 99%